Institute of Information and Communication Technologies - Muzik, Jozef (Communications - Scientific letters of the University of Zilina, 2003)
The roots of keeping computers and information technologies at the University of Žilina go back to 1967, whilst the Computer Centre was established as an independent part of the Department of Mathematics and Descriptive Geometry at the Faculty of Mechanical and Electrical Engineering. In 1982, the Computer Centre was transformed into the Institute of Computer Technology. In that time the institute serviced great mainframes where all computational needs of the university were solved and the first steps toward the university network had been done as well. The institute gradually extended its services as new technologies were emerging. In the year 2003 this all led to the new transformation and renaming of the institute into the Institute of Information and Communication Technologies. At present the institute provides support for all activities tied up with the information and communication technologies at the University of Žilina. Many services, the list of which follows, are provided.